Finite Element Analysis for Transverse Carpal Ligament Tensile Strain and Carpal Arch Area - Yao, Yifei (J Biomech, 2018)
Mechanics of carpal tunnel soft tissue, such as fat, muscle and transverse carpal ligament (TCL), around the median nerve may render the median nerve vulnerable to compression neuropathy. The purpose of this study was to understand the roles of carpal tunnel soft tissue mechanical properties and intratunnel pressure on the TCL tensile strain and carpal arch area (CAA) using finite element analysis (FEA). Manual segmentation of the thenar muscles, skin, fat, TCL, hamate bone, and trapezium bone in the transverse plane at distal carpal tunnel were obtained from B-mode ultrasound images of one cadaveric hand. Sensitivity analyses were conducted to examine the dependence of TCL tensile strain and CAA on TCL elastic modulus (0.125–10 MPa volar-dorsally; 1.375–110 MPa transversely), skin-fat and thenar muscle initial shear modulus (1.6–160 kPa for skin-fat; 0.425–42.5 kPa for muscle), and intratunnel pressure (60–480 mmHg). Predictions of TCL tensile strain under different intratunnel pressures were validated with the experimental data obtained on the same cadaveric hand. Results showed that skin, fat and muscles had little effect on the TCL tensile strain and CAA changes. However, TCL tensile strain and CAA increased with decreased elastic modulus of TCL and increased intratunnel pressure. The TCL tensile strain and CAA increased linearly with increased pressure while increased exponentially with decreased elastic modulus of TCL. Softening the TCL by decreasing the elastic modulus may be an alternative clinical approach to carpal tunnel expansion to accommodate elevated intratunnel pressure and alleviate median nerve compression neuropathy.